Hubungan Kadar sCD14, Jumlah Streptococcus Mutans, pH-Dapar, Fluor di Dalam Saliva dengan Kejadian Karies pada Anak Karyawan PTPN VIII Pangalengan Usia 12-15 Tahun - Dudi Aripin; Setiawan Natasasmita; Richata Fadil; Achmad Syawqie; Wazillah Nasserie (Indonesian Journal of Applied Sciences, 2011)
Dental caries is a multifactorial infection where there are four main etiological factors, i.e. salivary and teeth bacteria, carbohydrate, and time. The interaction among those factors can be described as four overlapped circles. The salivary sCD14 protein plays an important role in protecting hard and soft oral tissues from infection by pathogenic bacteria. There is a relationship between the presence of sCD14 in saliva of active caries patients and in caries-free patient which leads to an assumption that this salivary protein may play an important role in caries development process.  To look for an evidence of that assumption, a study on the relationship between salivary sCD14 level, number of Streptococcus mutans, Buffer pH, fluor in the saliva and dental caries incidence. The objective is to see the difference in the salivary sCD14 level, number of Streptococcus mutans, Buffer PH and fluor in the saliva as well as to analyze the correlation of those factors with high caries incidence. This study is an analytical observational study using “case control” design with children of PTPN VIII Pangalengan employees with an age range of 12-15 years old as the sample. The sample size was determined using the rule of thumb with a minimum of 80 samples. The selection of subjects was conducted using simple random sampling and the analysis in this study is performed using bivariate (t-test and X2 test) and multivariate (multiple logistic regression analysis). To determine the cut off point, an  ROC (Receiver Operating Characteristic) curve. The significance of the test results was determined based on a p value of < 0.005. The results of the study show that the sCD14 level in low caries subjects is higher than in the high caries subjects which is statistically and significantly different. The number of Streptococcus mutans bacteria in low caries subjects is fewer compared to the high caries subjects, which difference is statistically significant. Based on the results of the multiple logistic regression analysis, there is a correlation between sCD14 level, number of Streptococcus mutans, buffer-pH, fluor in saliva and the high incidence of caries. Those four factors strongly influence the high caries incidence  It is concluded that there is a strong correlation between sCD14 level number of Streptococcus mutans, buffer-pH, fluor in the saliva and high caries incidence. The risk factor with the highest influence towards caries incidence in this study is the fluor concentration in saliva.****Karies gigi merupakan penyakit infeksi multifaktorial yang disebabkan oleh empat faktor utama sebagai etiologi, yaitu gigi dan saliva, bakteri, karbohidrat dan waktu. Paduan faktor tersebut dapat digambarkan sebagai empat lingkaran yang saling tumpang tindih. Protein sCD14 di dalam saliva memegang peran penting dalam melindungi jaringan lunak dan keras di rongga mulut dari infeksi oleh bakteri patogen. Terdapat hubungan antara keberadaan sCD14 di dalam saliva antara penderita karies aktif dengan penderita bebas karies, hal ini menimbulkan dugaan bahwa protein sCD14 mungkin berperan penting dalam proses perkembangan karies. Untuk mengungkapkan hal tersebut diperlukan penelitian tentang hubungan kadar sCD14, jumlah Streptococcus mutans, pH-bufer, fluor di dalam saliva dengan kejadian karies. Tujuannya yaitu untuk melihat perbedaan kadar sCD14, jumlah Streptococcus mutans, pH-bufer, fluor di dalam saliva serta menganalisis hubungan faktor tersebut dengan kejadian karies tinggi. Penelitian ini bersifat observasional analitik dengan rancangan “kasus kontrol”. Sampel penelitian adalah anak karyawan PTPN VIII Pangalengan usia 12-15 tahun. Ukuran sampel ditentukan secara ‘rule of thumb’ dengan jumlah sampel minimal 80. Pemilihan subjek dilakukan secara simple random sampling. Pada penelitian ini digunakan analisis bivariable (uji t dan uji Chi Kuadrat), multivariable (regresi logistik ganda), dan untuk menentukan cut off point digunakan kurva ROC (Receiver Operating Characteristic). Kemaknaan hasil uji ditentukan berdasarkan nilai p≤0,005. Hasil penelitian kadar sCD14 pada  karies rendah lebih tinggi bila dibandingkan dengan karies tinggi, secara statistik berbeda dan bermakna. Jumlah Streptococcus mutans pada  karies rendah lebih sedikit bila dibandingkan dengan karies tinggi, secara statistik berbeda sangat bermakna. Berdasarkan hasil analisis regresi logistik ganda menunjukkan adanya hubungan kadar sCD14, jumlah Streptococcus mutans, pH-bufer, fluor di dalam saliva dan kejadian karies tinggi, keempat faktor tersebut berpengaruh kuat terhadap kejadian karies tinggi. Simpulan terdapat hubungan yang kuat antara kadar sCD14, jumlah Streptococcus mutans, pH-bufer, fluor di dalam saliva dengan kejadian karies tinggi. Faktor risiko yang berpengaruh paling kuat terhadap kejadian karies pada penelitian ini adalah konsentrasi fluor di dalam saliva.